Identification and characterisation of novel human Y-chromosomal microsatellites from sequence database information - Ayub, Qasim (Oxford University Press, 2000)
1.33 Mb of sequence from the human Y chromosome was searched for tri- to hexanucleotide microsatellites. Twenty loci containing a stretch of eight or more repeat units with complete repeat sequence homogeneity were found, 18 of which were novel. Six loci (one tri-, four tetra- and one pentanucleotide) were assembled into a single multiplex reaction and their degree of polymorphism was investigated in a sample of 278 males from Pakistan. Diversities of the individual loci ranged from 0.064 to 0.727 in Pakistan, while the haplotype diversity was 0.971. One population, the Hazara, showed particularly low diversity, with predominantly two haplotypes. As the sequence builds up in the databases, direct methods such as this will replace more biased and technically demanding indirect methods for the isolation of microsatellites.